Effects of 3 g of soluble fiber from oats on lipid levels of Asian Indians - a randomized controlled, parallel arm study - Seema Gulati; Anoop Misra; Ravindra M Pandey (Lipids in Health and Disease, 2017)
Abstract Background Cardiovascular diseases are more prevalent and severe in Asian Indians. Simple diet-based strategies are important for prevention of cardiovascular diseases.The aim of the present study was to evaluate the effects of oats consumption on lipid parameters in mildly hypercholesterolemic Asian Indians living in India. Methods A short-term, prospective, open-labeled, randomized controlled, parallel group study was conducted. Mildly hypercholesterolemic (total cholesterol >200 mg/dL and <240 mg/dL) subjects (n = 80) were randomized into two groups: intervention (n = 40) and usual diet (n = 40). Sample size was calculated for a two-group parallel superiority randomized control trial. Out of 80 enrolled subjects 69 subjects completed the study; 33 in the control group and 36 in the intervention group. In the intervention group, patients were served 70 g of oats twice a day in the form of porridge and upma (A thick porridge from oats with seasonings and vegetables) under observation at the study site. Lipid parameters were assessed at baseline and after 4 weeks of intervention. Results There was a reduction of 3.1% in total cholesterol levels in the control group as against 8.1% reduction in the intervention group (p < 0.02). Greater reductions were also seen in low-density lipoprotein cholesterol in the intervention group (11.6%) as compared to control group (4.1%, p < 0.04) over a period of 28 days. Conclusion Daily consumption of 3 g of soluble fiber from 70 g of oats leads to beneficial effects on the lipid parameters, specifically total cholesterol and low-density lipoprotein cholesterol in hypercholesterolemic Asian Indians. Large scale studies over a longer period of intervention are required to further establish the cholesterol-lowering effect of oat fiber. Trial registration The study was retrospectively registered at clinicaltrials.gov (dated: 25th Februrary.2015) with registration number NCT02376660 .